2017
DOI: 10.1073/pnas.1615269114
|View full text |Cite
|
Sign up to set email alerts
|

Distributed representation of context by intrinsic subnetworks in prefrontal cortex

Abstract: Human prefrontal cortex supports goal-directed behavior by representing abstract information about task context. The organizational basis of these context representations, and of representations underlying other higher-order processes, is unknown. Here, we use multivariate decoding and analyses of spontaneous correlations to show that context representations are distributed across subnetworks within prefrontal cortex. Examining targeted prefrontal regions, we found that pairs of voxels with similar context pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 62 publications
(67 reference statements)
4
15
0
Order By: Relevance
“…These subnetworks are task specific and seem to be specialized for the particular demands and requirements of a concrete task. Our result confirms the earlier report by Waskom and Wagner ( 2017 ) that lateral prefrontal cortex voxels coding for particular task relevant stimulus features show stronger functional connectivity during subsequent rest. We here show that this is also true for the subsets of voxels from the multiple demand networks, both within and between the nodes of this network.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These subnetworks are task specific and seem to be specialized for the particular demands and requirements of a concrete task. Our result confirms the earlier report by Waskom and Wagner ( 2017 ) that lateral prefrontal cortex voxels coding for particular task relevant stimulus features show stronger functional connectivity during subsequent rest. We here show that this is also true for the subsets of voxels from the multiple demand networks, both within and between the nodes of this network.…”
Section: Discussionsupporting
confidence: 93%
“…In vivo parcellation studies have shown that connectivity similarity analyses allow to further break up these territories into smaller fields, each with a unique connectivity profile resembling the organization of the larger network to which they belong, but uniquely different across individuals and species (Goulas et al 2012 , 2017 ; Sallet et al 2013 ; Braga and Buckner 2017 ). Our current findings, together with those of some other studies (Park et al 2017 ; Waskom and Wagner 2017 ), go a step further by showing that even within this connectionally more homogeneous fields, unique and function-specific subpatterns of connectivity can be demonstrated to exist.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As correlations with the pool are stronger than across pools, they have as effect to amplify the signal within the pool and to help a reliable transmission of the signal. On a coarser spatial and temporal scale, it has been demonstrated that patterns of spontaneous activity reflect the functional architecture of the cortex [24,25,26], including the representation of abstract information, such as rules or goals [27]. Finding the same organization in V4 on a smaller spatial scale and during active classification of stimuli opens up the possibility that correlation structure also actively supports processing of stimuli in abstract categorization tasks.…”
Section: Discussionmentioning
confidence: 99%
“…MVPA has been applied to fMRI data from all over the brain, and the prefrontal cortex is no exception. Several studies have reported statistically reliable classification of task rule and other task-relevant variables from regions within prefrontal cortex [36][37][38][39][40][41] .…”
Section: Introductionmentioning
confidence: 99%